Detection of HBV-DNA and Its Correlation with the HBeAg/Anti-HBe Serological Status in HBsAg-positive Patients - Haris Widita; Soewignjo Soemohardjo; Zainul Muttaqin; Putu Aditya Wiguna; Shelly Olivia Rhamdiani; Mahendra Wijaya; Stephanus Gunawan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2012)
Background: In the past years, HBeAg and anti-HBe status in individuals with positive HBsAg were often correlated to viral replication. This study was aimed to find correlation between the HBV viremia and HBeAg/anti-HBe serological status in HBsAg-positive individuals. Method: An observational-analytic design was performed in this study. The sera of all positive HBsAg patients at Biomedika Hospital Laboratory were collected and examined for HBeAg and anti-HBe using immunochromatography technique between January and April 2012. The sampling method was purposive sampling. Afterwards, the sera were examined for HBV-DNA by polymerase chain reaction (PCR). Results: Sufficient amount of sera were collected from 44 patients consisting of 33 males and 11 females. The mean age was 15-68 years. Positive HBeAg and negative anti-HBe status was found in 11 (42%) patients. Negative HBeAg and positive anti-HBe was found in 26 (59.1%) patients. Both HBeAg and anti-HBe were negative in 7 (16.3%) patients. HBV-DNA was detected in all 11 (100%) patients with positive HBeAg and negative anti-HBe. HBV-DNA was also detected in 11 (42%) patients with negative HBeAg and positive anti-HBe. However, there was only one patient (14.3%) with both negative HBeAg and anti-HBe status, who had detectable HBV-DNA. Conclusion: Positive HBeAg can be used as an indicator of viremia, but negative HBeAg cannot be used as an indicator of the absence of viremia without further HBV-DNA testing. Patients with negative HBeAg and positive HBV-DNA were suspected for having pre-core mutant. Keywords: HBV-DNA, positive HBsAg, HBeAg, anti-HBe, pre-core mutant